Cancer CRC: A Comprehensive Cancer Core Transcriptional Regulatory Circuit Resource and Analysis Platform - Wei, Ling; Chen, Jiaxin; Song, Chao; Zhang, Yuexin; Zhang, Yimeng; Xu, Mingcong; Feng, Chenchen; Gao, Yu; Qian, Fengcui; Wang, Qiuyu; Shang, Desi; Zhou, Xinyuan; et al. (Frontiers in Oncology, 2021)
A core transcriptional regulatory circuit (CRC) is a group of interconnected auto-regulating transcription factors (TFs) that form loops and can be identified by super-enhancers (SEs). Studies have indicated that CRCs play an important role in defining cellular identity and determining cellular fate. Additionally, core TFs in CRCs are regulators of cell-type-specific transcriptional regulation. However, a global view of CRC properties across various cancer types has not been generated. Thus, we integrated paired cancer ATAC-seq and H3K27ac ChIP-seq data for specific cell lines to develop the Cancer CRC (http://bio.liclab.net/Cancer_crc/index.html). This platform documented 94,108 cancer CRCs, including 325 core TFs. The cancer CRC also provided the “SE active core TFs analysis” and “TF enrichment analysis” tools to identify potentially key TFs in cancer. In addition, we performed a comprehensive analysis of core TFs in various cancer types to reveal conserved and cancer-specific TFs.